Harmful working conditions as a risk factor for the development of occupational morbidity in auxiliary professions workers - Sevalniev, A. I.; Sharavara, L. P. (Zaporozhye Medical Journal, 2019)
The purpose of the work was to assess the occupational health risk for workers exposed to harmful conditions at the auxiliary workshop. Materials and methods. The hygienic assessment of working environment at 48 workplaces of mechanical shop turners was conducted. 611 researches of chemical and physical factors of the working environment and 448 analyses of workplace air for fine dust concentrations of PM4 and PM10 fractions were performed. Rates and patterns of the temporary work incapacity for 3 years were determined and indices of professional risk were calculated: the rate of disease (R), the relative risk (RR), the attributive risk (AR) and population attributable risk (PAR). Results. According to the results of the obtained data, it was determined that working conditions of the mechanical shop workers corresponded to the grade 3 of the first degree of harmful exposure and were characterized by a moderate degree of anticipated occupational risk. Morbidity rate with a temporary disability was 102.28 ± 8.09 cases and 1226.72 ± 100.3 days of disability per 100 workers, that was characterized as above the average and high according to the E. L. Notkin scale of temporary work disability rates. Respiratory, digestive, musculoskeletal system and connective tissue diseases accounted the largest share in the morbidity pattern. Based on indices of occupational risk, it was found that the very high degree of work related pathology characterized respiratory diseases (RR = 8.89 at CI 95 %, 3.93–20.12), diseases of the ear and mastoid process (RR = 7.9 at CI 95 %, 1.45–43.16); high degree was typical for diseases of the skin and subcutaneous tissue (RR = 3.16 at CI 95 %, 1.21–8.26), diseases of the eye and adnexa (RR = 2.43 at CI 95 %, 0.55–10.78); medium degree – infectious and parasitic diseases (RR = 1.98 at CI 95 %, 0.25–15.80), diseases of the genitourinary system (RR = 1.94 at CI 95 %, 0.89–4.26), diseases of the digestive system (RR = 1.68 at CI 95 %, 0.88–3.23), musculoskeletal system and connective tissue diseases (RR = 1.57 at CI 95 %, 0.82–3.00). Conclusions. According to calculated occupational risk, the list of work related morbidity was identified for mechanical shop workers, in particular for turners. The proportion of diseases among the workers of mechanical shop (AR 54.66–89.92 %) exceeded the indicators in the control group (PAR 26.58–56.02 %), which confirms the influence of occupational hazards on the health of workers. The preventive measures aimed at reducing the risks of occupational diseases development in workers have been proposed.